Schoology-Aided Instruction: Measuring the Effectiveness for Student-Teachers’ Reading Comprehension Achievement - Firdaus, Masagus; Mayasari, Santi (Journal of Languages and Language Teaching, 2022)
This study was a quasi-experimental research and oriented to measure the effectiveness for student-teachers’ reading comprehension achievement. There were 80 student-teachers who joined and were grouped into experimental and control groups. They were treated for eight meetings. Both pretest and posttest instruments were integrated for collecting the data. Both paired and independent t-tests were employed to know improvement of the two groups. The findings showed that in pretest, both of groups encountered problems related to reading comprehension. However, after being treated with this Schoology learning management system (LMS) for several meetings, experimental group students gained better achievement in reading comprehension comparing to control group. Mean scores of experimental group (75.250) was bigger than control group gained (61.875). By the same token, the F-test score (0.392) with df (78) and sig. value (0.000) informed about different qualities gained by both groups, i.e., experimental and control. In a nutshell, the integration of Schoology LMS is more effective in increasing students’ reading comprehension comparing to conventional mode of learning.